2014
DOI: 10.1194/jlr.e051276
|View full text |Cite
|
Sign up to set email alerts
|

Robust validation of methylation levels association at CPT1A locus with lipid plasma levels

Abstract: There is increasing enthusiasm regarding the use of biobanked whole blood DNA as a model to discover methylation marks associated with biological phenotypes and generate novel mechanistic hypotheses ( 1 -3 ). DNA methylation has a critical role in cell functions and is cell-type specifi c. Such cell specifi city makes DNA methylation particularly challenging for epidemiological epigenetic investigations because disease relevant cell types might not be accessible due to practical issues such as availability, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…In fact, many of these same CpGs are associated with lipid‐related traits from specific EWAS performed for these measures, presumably because of their relationship to the development of adiposity or downstream‐induced epigenetic changes from BMI‐associated altered blood lipid profiles. Four of the ten DMPs were significantly related to triglyceride levels in a recent study by Dekkers et al , as well as in earlier and contemporary lipid studies . Furthermore, a study by Kriebel et al found that four of these CpGs are related to glucose‐related phenotypes .…”
Section: Ewas For Obesity (Bmi) In Peripheral Bloodmentioning
confidence: 71%
“…In fact, many of these same CpGs are associated with lipid‐related traits from specific EWAS performed for these measures, presumably because of their relationship to the development of adiposity or downstream‐induced epigenetic changes from BMI‐associated altered blood lipid profiles. Four of the ten DMPs were significantly related to triglyceride levels in a recent study by Dekkers et al , as well as in earlier and contemporary lipid studies . Furthermore, a study by Kriebel et al found that four of these CpGs are related to glucose‐related phenotypes .…”
Section: Ewas For Obesity (Bmi) In Peripheral Bloodmentioning
confidence: 71%
“…Methylation at the top CPT1A locus explained 12% of TG variation in the discovery cohort (Genetics of Lipid Lowering Drugs and Diet Network (GOLDN), CD4+ lymphocytes, n=991) and 6% in the replication cohort (Framingham Heart Study, whole blood, n=1261) [12]. Subsequent studies have replicated the observed association with lipids [7, 15, 16] and lipoprotein subfraction profiles [17], as well as linked CPT1A methylation with obesity traits [18, 19], metabolic syndrome [20], and hypertriglyceridemic waist [21] in diverse populations. Interestingly, CPT1A loci were also shown to be differentially methylated in Dutch Hunger Winter survivors exposed to famine in utero , associating with both birth weight and serum LDL cholesterol levels later in life [22] and providing a possible mechanism for the well-known adverse metabolic sequelae of prenatal malnutrition.…”
Section: Dna Methylationmentioning
confidence: 99%
“…All subjects had a documented history of VT, were free of chronic diseases, and were free of inherited thrombophilia including: anti-thrombin, protein C and protein S deficiencies and homozygosity for the Factor V Leiden and Factor II G20210A mutations. For the methylation project, 349 MARTHA patients were randomly selected for DNA methylation analysis 173,174,175,176 .…”
Section: The Martha Cohortmentioning
confidence: 99%